The Impact of Information & communication Technology and Supply Chain Supply chain knowledge management on Lead Time - Chairit Thongrawd; Kriengsak Khantanapha; Thanakorn Thanathanchuchot; Puttithorn Jirayus (International Journal of Supply Chain Management, 2020)
Abstract- The objective of the present study is to examine the impact of supply chain knowledge management and information and communication technology on lead time of the retail sector of Indonesia. Additionally, mediating role of Responsive Supply Chain is examined in the present study as well. For the present study, Data was collected in the form of questionnaire from the customers of retail sector of Indonesia. A total 340 questionnaire were distributed among the manufacturing firms in the Indonesia. The response rate of the current study is turned out to be 67.5 percent. For analysis of the data gathered, the Partial Least Squares (PLS) software was chosen for carrying out statistical analysis of the collected data, followed by the presentation of the outcomes. The results of the study support all of the proposed hypothesis. The current study is important for the policy makers and practitioners of supply chain and retail sector to use the supply chain knowledge management tactics and information and communication technology so the lead time can be improved.